SCAFFOLDINGAND REINFORCEMENT: USING DIGITAL LOGBOOKS IN LEARNING VOCABULARY - Salma Hasan Almabrouk Khalifa; Ahmad Affendi Shabdin (Proceedings of The ICECRS, 2016)
Reinforcement and scaffolding are tested approaches to enhance learning achievements. Keeping a record of the learning process as well as the new learned words functions as scaffolding to help learners build a comprehensive vocabulary. Similarly, repetitive learning of new words reinforces permanent learning for long-term memory. Paper-based logbooks may prove to be good records of the learning process, but if learners use digital logbooks, the results may be even better. Digital logbooks with an extended page with hyperlinked information on word-knowledge may work both ways – as scaffolding to learning as well as reinforcement to the learning process. In the present paper the researcher has suggested for the development of a software called ‘Vocabulary log book,’ which combines the features of Microsoft Word, online dictionary and online grammar books, so that the information needed by learners of a foreign language to learn its lexicon is available on a single page. The researcher believes that such a page will help learners master the new words quickly and efficiently.